Slums and low income market of informal and irregular housing (2009)
The commercialization of irregular property, particularly in clandestine slum quarters and land divisions, between low income populations expresses one of the cruelest faces of the reproduction of the urban space process in our cities. In the metropolitan region of Sao Paulo –RMSP– this type of transaction is characterized as a segment of used property market for low income, contributing excessively in the process of unequal structuring of the metropolis, concentrating the poorest population in lacking of infrastructure spaces. This segment of the market can be captures by diversified forms of housings and places constructed by these populations, and identified by its strategies of survival. Perhaps this form of access to precarious housing, without ownership security and acquired through the mechanisms of the market is the most important characteristic of the dismounting of the State. This work intends to analyze the functioning a sector of the real estate market for low income population in the RMSP, that produces, commercializes and acquires its properties in favelas.